Evaluación del tratado de libre comercio entre Colombia y México en el período 2011-2019. (2022)
Free trade agreements have been mechanisms by which two or more countries have carried out commercial, social, political and cultural agreements in order to promote economic development and the international economy, there are multiple functions and objectives that a country can have. free trade agreement, all taking into account the interests that were raised at the time of the negotiation, in the particular case of the free trade agreement between Colombia and Mexico there was already a precedent the G3 made up of Colombia, Mexico and Venezuela which in a At first it was not a trade agreement but rather served more as a bridge between the European market and the Caribbean countries, but over time it became an agreement to trade goods and services with low tariffs. Once Venezuela made its exit official, the agreement was dissolved, however, both Colombia and Mexico agreed to continue with the commercial relationship, so a new treaty was negotiated based on the previous one and adding new goods and services to the tax relief. tariff, establish new parameters to make it easier to carry out foreign trade operations, among which the provision of information, financial and security services to investors stand out.